Pendampingan Praktek Magang Pada Industri Jasa Keuangan oleh Mahasiswa Program Studi Keuangan dan Perbankan Universitas Siliwangi - Dedeh Sri Sudaryanti; Tine Badriatin; Noneng Masitoh (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2020)
Community service is carried out by providing apprenticeship practices to PT. Reliance Sekuritas Indonesia, Tbk., Tasikmalaya Representative Office as one of the companies cooperating with Siliwangi University through cooperation in the Indonesia Stock Exchange Investment Gallery - FEB UNSIL - RELI. One of the objectives of this internship practice is to be able to open up opportunities for Siliwangi University Finance and Banking Study Program students in applying the theory and knowledge learned by students, especially internships during lectures to the reality of practical work. The method used is the Job Training in capital market companies. Therefore this internship training assistance is carried out with capital market lecturers. The internship practices carried out at capital market companies were carried out by 3 participants for 30 calendar days with an effective period of 22 working days. As for the results of the internship practices, interns can learn directly the stock trading system on the Indonesia Stock Exchange by observing the live trade exchanges and the apprentice can find out how to administer the marketing of stock account opening.